Recurrent Adenomatous Neuroendocrine Tumor of the Middle Ear: A Diagnostic Challenge - J. Vilain; J.-C. Degols; S. Ledeghen (Case Reports in Otolaryngology)
Middle ear adenomatous neuroendocrine tumor (MEANT) poses a diagnostic challenge. Clinical symptoms are nonspecific. Definite diagnosis is made by histopathological analysis of the tumor after a complete surgical resection based on an extensive computed tomography/magnetic resonance imaging (CT/MRI). Controversial terminology of the neoplasm arises from the differentiation of this tumor composed of both endocrine and exocrine glands. Middle ear (ME) localization is rare and less aggressive than gastrointestinal tract or lung localizations. Nevertheless, clinical and CT/MRI analyses are necessary follow-ups for preventing or detecting recurrence or metastasis. A case of a female patient aged 26 with recurrent middle ear neuroendocrine adenoma is presented herein.